1993
DOI: 10.1016/0014-5793(93)80226-k
|View full text |Cite
|
Sign up to set email alerts
|

Receptor phage

Abstract: In this paper we demonstrate that phage display technology is a suitable system for studying the interaction between the high-affinity receptor for IgE (FcsRI) and IgE. The a subunit extracellular domains of the human receptor were expressed on the surface of filamentous phage Ml3 fused to the carboxyl-terminal part of the gene III protein @III). Two constructs were made, the first with both the Ig-like domains of the receptor a chain and the second with only the C-terminal domain. The fusion genes were cloned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…However, the role of the first domain is not clear in Fc⑀RI nor indeed in any Fc receptor. Analyses to date have variously indicated that domain one is necessary for optimal binding (1)(2)(3), that it has a possible role in direct interaction with IgE (4,5), and that it provides a supportive role in maintaining receptor integrity (1,2). The structural reasons for this are not apparent.…”
mentioning
confidence: 99%
“…However, the role of the first domain is not clear in Fc⑀RI nor indeed in any Fc receptor. Analyses to date have variously indicated that domain one is necessary for optimal binding (1)(2)(3), that it has a possible role in direct interaction with IgE (4,5), and that it provides a supportive role in maintaining receptor integrity (1,2). The structural reasons for this are not apparent.…”
mentioning
confidence: 99%
“…Extensive efforts were hence attempted to produce Cε3 and D2 as isolated domains or as engineered variants (e.g., fusion proteins) [27, 28, 29, 30, 31]. Engineering started when the 3D structure of IgE Fc and FcεRIα D1D2 was still unknown.…”
Section: A Synergic Ensemblementioning
confidence: 99%
“…The protein reached the cell surface (probed by an mAb recognizing a short peptide of D2), yet IgE binding was undetectable and membrane D2 was not recognized by FcεRIα-specific mAbs with IgE inhibitory activity, suggesting that the IgE binding site was not folded properly [27]. In the same year, two independent groups reported the expression of D2 on the surface of M13 bacteriophage as a fusion to protein gIII [28, 29], followed very recently by a D2 mutagenesis and phage display screening study [33]. Phage gIII protein fusion appeared as a more effective strategy to display D2, even though D2 binding to IgE was considerably reduced compared to phage-displayed D1D2 [28, 29].…”
Section: A Synergic Ensemblementioning
confidence: 99%
See 2 more Smart Citations